Detection of the toxic substance dibutyl phthalate in Antarctic krill. Issue 6 (31st July 2017) - Han, Xiangning; Liu, Daicheng
Abstract: High-performance thin layer chromatography was performed to investigate the potential presence of four phthalic acid esters, dimethyl phthalate (DMP), diethyl phthalate (DEP), dibutyl phthalate (DBP) and dioctyl phthalate (DEHP), in Antarctic krill. The results revealed that in freeze-dried Antarctic krill levels of DBP (0.1043±0.0005 mg g -1 (104.3±0.05 mg kg -1 )) were high. The structure of DBP in Antarctic krill was determined by gas chromatography-mass spectrometry. Its existence is of concern based on demonstrated harmful effects to animals and plants as Antarctic krill is a key part of the food chain in Antarctic coastal marine ecosystems. The adverse effects of DBP on Antarctic krill and the source of DBP should be explored in further research.